2013
DOI: 10.1021/ef401629d
|View full text |Cite
|
Sign up to set email alerts
|

JP-5 and HRJ-5 Autoignition Characteristics and Surrogate Modeling

Abstract: A heated rapid compression machine has been used to investigate the autoignition behavior of JP-5 and camelina-based hydrotreated renewable jet (HRJ-5) fuels. Testing was conducted at low temperatures (T c = 627–733 K), low-to-moderate pressures (p c = 5, 10, and 20 bar), and lean (ϕ = 0.25 and 0.50) and stoichiometric mixtures in air. The HRJ-5 fuel, which is 99% paraffinic, exhibited greater reactivity than the JP-5 fuel in the form of shorter ignition delays. The HRJ-5 fuel also exhibited transition into th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 28 publications
4
14
0
Order By: Relevance
“…These surrogates were used to represent both JP-8 and JP-5 because of the similarities seen in low temperature ignition between Jet-A and conventional military fuels in studies we have conducted previously. 6 Figure 3 shows the results of each surrogate in comparison to the measured experimental trace, indicating closest agreement to experimental results for both the Dooley and Ranzi mechanisms. The Aachen mechanism fails to show ignition within the time frame for both ϕ = 0.25 and 0.5 cases.…”
Section: Chemical Kinetics Modelingsupporting
confidence: 60%
See 2 more Smart Citations
“…These surrogates were used to represent both JP-8 and JP-5 because of the similarities seen in low temperature ignition between Jet-A and conventional military fuels in studies we have conducted previously. 6 Figure 3 shows the results of each surrogate in comparison to the measured experimental trace, indicating closest agreement to experimental results for both the Dooley and Ranzi mechanisms. The Aachen mechanism fails to show ignition within the time frame for both ϕ = 0.25 and 0.5 cases.…”
Section: Chemical Kinetics Modelingsupporting
confidence: 60%
“…Another recent study by Allen et al focused on USN jet fuel, JP-5, and camelina-based USN fuel equivalent, HRJ-5. The lean, low temperature rapid compression machine (RCM) test conditions confirmed the enhanced reactivity of the paraffinic HRJ fuels as seen in prior studies . Kinetic models from the Aachen group, developed by Honnet et al, and Princeton, by Dooley et al, were used to examine model agreement with observed experimental results.…”
Section: Introductionmentioning
confidence: 55%
See 1 more Smart Citation
“…Overall, the shock tube and RCM data correlate favorably, with the exception of HRJ-5 and LINPAR 1416V where the RCM predicts faster ignition than the shock tube. This phenomenon has been previously noted [3,4], where ignition delays measured in RCMs can be shorter than observed in shock tubes for ignition delay times less than $8 ms due to preignition chemistry occurring prior to TDC, particularly for highly reactive n-paraffinic fuels such as HRJ-5 and LINPAR 1416V.…”
Section: Comparison Of Conventional and Alternative Fuels In Intermedsupporting
confidence: 59%
“…Understanding of the chemical kinetic behavior of alternative fuels, for example macroscopically exemplified through ignition delay, flame speed, and extinction limits, is needed for combustion model development. Kinetic targets for fuel characterization and model development have only become recently available in the literature for complex multi-component fuels, including autoignition studies for conventional, HRJ, and FT fuels [3][4][5][6][7]; however, little work has been performed regarding blends of conventional and alternative fuels. Additionally, the influence of fuel composition/structure on autoignition is sparse in the literature, particularly at lean conditions, that are becoming increasingly attractive for achieving reductions in production of harmful emissions.…”
Section: Introductionmentioning
confidence: 99%